Hipertensi: Gambaran Umum - Naufal Rivo Aditya; Syazili Mustofa (MAJORITY, 2023)
Chronic disease is a worldwide health issue. The prevalence of chronic disease is 6,7 billion people worldwide, and has increased over the time. Chronic disease is a noncommunicable disease, but chronic disease is a persistant disease and resulting in substansial years of life lost. One of the chronic diseases is hypertension or high blood pressure. The prevalence of hypertension is 1,2 billion people worldwide and increasing due to an aging population and increasing prevalence of obesity. Hypertension is multifactorial disease involving genetic factors and environmental factors. Aparts from these two factors, behaviors factors can be increasing risk factor for hypertension, such as smooking and excess salt consumption. AHA (American Heart Association) hypertension guidelines, hypertension is diagnosed when blood pressure is consistently >130 for systolic pressure, and or >80 mmHg for diastolic pressure. Hypertension have a significant effects due to CVD (Cardiovascular disease) such as hearth failure, myocardial infarction, stroke and death. Hypertension in older adults have a adverse effects and exacerbated by a decrease in body function and quality, such as mechanical hemodynamic changes, arterial stiffness, neurohormonal and declining renal function, so the management strategies for hypertension in older adults must consider from various aspects, such as comorbidities factors, pyscho-social factors. The management strategies for hypertension can be used non-pharmacological therapy to reduce the risk of hypertension severity and provide appropriate pharmacological therapy according to the patient’s condition, so that it can provide appropriate results.